2014
DOI: 10.1097/bcr.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Seizure Disorders in Burn Injury and Outcome in Sub-Saharan Africa

Abstract: OBJECTIVE Patients with epilepsy have higher incidence and severity of burn injury. Few studies describe the association between epilepsy and burns in low-income settings, where epilepsy burden is highest. We compared patients with and without seizure disorder in a burn unit in Lilongwe, Malawi. METHODS We conducted a retrospective study of patients admitted to the Kamuzu Central Hospital burn ward from July 2011 to December 2012. Descriptive analysis of patient characteristics and unadjusted and adjusted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Among studies with adults only, men are found to be more at risk especially between 20 and 30 years of age [100] , [102] , [103] , [105] , [106] . Scald injuries (usually in children) and flame injuries (usually in adults) are the most common types of injuries [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among studies with adults only, men are found to be more at risk especially between 20 and 30 years of age [100] , [102] , [103] , [105] , [106] . Scald injuries (usually in children) and flame injuries (usually in adults) are the most common types of injuries [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , …”
Section: Resultsmentioning
confidence: 99%
“…Many burn injuries occur during the cool/dry/windy months [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [68] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [100] . Epilepsy is a common contributing factor to burn injuries [47] , [50] , [62] , [63] , [64] , [65] , [66] , [68] , [74] , [100] , [107] .…”
Section: Resultsmentioning
confidence: 99%
“…26 Similarly, our incidence of partial seizure was comparable to standard pattern. Boschini L et al 21 in their study found that patients with epilepsy have higher incidence and severity of burn injuries. Jang YC et al 22 in their study mentioned that in epileptic burns, the most commonly associated seizure type was generalised tonic-clonic followed by absence and complex partial.…”
Section: Type Of Seizurementioning
confidence: 92%
“…The inhibitory network is recruited by the primary somatosensory cortex-orbitofrontal-cingular-amygdalar network allowing the impact of emotional/cognitive changes [20]. The anti-analgesic effect of PAG-activation has been used in deep brain-stimulation treatment of chronic pain in humans [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%